A novel method for the quantification of industrial and municipal waste materials for environmental hazard assessment - Arifin, M.H. (Elsevier B.V., 2021)
A novel methodological approach was developed to quantified the volume of industrial waste desposal (IWD) site, combined with municipal waste materials (MWM), through the integration of a non-invasive, fast, and less expenssive RES2-D Electrical Resistivity Technique (ERT), using Wenner-Schlumberger electrode array geophysical method with Oasis Montaj software. Underground water bearing structures, and the eco-system are being contaminated through seepage of the plumes emanating from the mixtures of the industrial waste materials (IWM), made of moist cemented soil with municipal solid wastes (MSW) dumped at the site. The distribution of the contiminant hazardous plumes emanating from the waste materials' mixtures within the subsurface structural lithological layers was clearly map and delineated within the near-surface structures, using the triplicate technique to collect samples of the soil with the waste mixtures, and the water analysis for the presence of dissolved ions. The deployed method helped to monitor the seepage of the contaminant leachate plumes to the groundwater aquifer units via the ground surface, through the subsurface stratum lithological layers, and hence, estimation of the waste materials' volume was possibly approximated to be 312,000 m3. In summary, the novel method adopted are as presented below: â¢ The novel method is transferable, reproduce-able, and most importantly, it is unambiguous technique for the quantification of environmental, industrial and municipal waste materials. â¢ It helps to map the distribution of the plumes emanating from the waste materials' mixtures within the subsurface structural lithological layers that was clearly delineated within the near-surface structures underlain the study site. â¢ The procedure helped in the monitoring of leachate contaminants plumes seepages into the surface water bodies and the groundwater aquifer units, via the ground surface, through to the porous subsurface stratum lithological layers. Â© 2020